Double-Crop Sunflower Cost-Return Budget in North Central and Eastern Kansas - Fausett, Marvin R.; Dhuyvetter, Kevin C. (My University, 1997)
This publication provides estimated cost and returns for forward farm planning for a double-crop sunflower production system in north central and northeastern Kansas.
MF2145_1997_10
Keywords: MF2145; Crops; Economics; MF